2022
DOI: 10.1093/hropen/hoac016
|View full text |Cite
|
Sign up to set email alerts
|

The mid-secretory endometrial transcriptomic landscape in endometriosis: a meta-analysis

Abstract: Study Question Do women with endometriosis have a different endometrial gene expression profile at the time of embryo implantation than women without endometriosis? Summary Answer The endometrial gene expression profile of women with endometriosis differs from that of women without endometriosis at the mid-secretory phase, although the differences are small. What Is Known Alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
2
5
0
Order By: Relevance
“…Our observation that there are only very few differences in eutopic endometrium with and without endometriosis is supported by a recently published meta-analysis, which did not show a single differently expressed gene in the mid-secretory phase [46]. Remarkably two other studies about miRNAs [47] and methylation patterns [48] also reported similar results.…”
Section: Discussionsupporting
confidence: 87%
“…Our observation that there are only very few differences in eutopic endometrium with and without endometriosis is supported by a recently published meta-analysis, which did not show a single differently expressed gene in the mid-secretory phase [46]. Remarkably two other studies about miRNAs [47] and methylation patterns [48] also reported similar results.…”
Section: Discussionsupporting
confidence: 87%
“…HTR2B is related to neovascularization and immunomodulation as well as neurotransmission ( 47 ), indicating that it could be involved in the pathogenesis of endometriosis. MAOA is a putative endometrial receptivity biomarker, which is also linked to endometriosis ( 48 ). PPP1R13L is a member of the apoptosis-stimulating proteins of the p53 ( ASPP ) family and was identified as a novel RelA-associated inhibitor (RAI) that binds to the NF-κB subunit p65/RelA and inhibits its transcriptional activity ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…These factors include alterations in the balance of proinflammatory and anti-inflammatory cytokines, changes in the composition and/or activity of specific endometrial immune cells, and aberrant expression of adhesion molecules at the implantation site [39]. Recent studies have, in fact, shown that women with endometriosis present dysregulation of key endometrial receptivity-specific genes often belonging to immunological pathways [40]. A meta-analysis of the endometrial transcriptome has shown that women with endometriosis exhibit a pro-inflammatory profile characterized by increased levels of uterine natural killer (uNK) cells in the eutopic endometrium [41].…”
Section: Comparison With the Existing Literaturementioning
confidence: 99%